1984
DOI: 10.1021/bi00310a010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of an octanucleotide containing the EcoRI recognition sequence with a phosphorothioate group at the cleavage site

Abstract: The synthesis and characterization of an octanucleotide, d(GGsAATTCC), containing the recognition sequence of the EcoRI restriction endonuclease with a phosphorothioate internucleotidic linkage at the cleavage site are described. Two approaches for the synthesis of the RP and SP diastereomers of this octamer by the phosphite method are presented. The first consists of the addition of sulfur instead of H2O to the phosphite at the appropriate position during chain elongation. This method results in a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(108 citation statements)
references
References 42 publications
4
103
1
Order By: Relevance
“…Many examples (17,19,30,61) have shown that R p -oligonucleotide phosphorothioates elute before the S p on reverse phase columns using triethylammonium acetate buffers. This was found here in every case, and the faster elution of R p -isomers was also maintained when the buffer was altered to morpholine acetate.…”
Section: Synthesis Of Phosphorothioate-containing Oligonucleotides-mentioning
confidence: 99%
See 3 more Smart Citations
“…Many examples (17,19,30,61) have shown that R p -oligonucleotide phosphorothioates elute before the S p on reverse phase columns using triethylammonium acetate buffers. This was found here in every case, and the faster elution of R p -isomers was also maintained when the buffer was altered to morpholine acetate.…”
Section: Synthesis Of Phosphorothioate-containing Oligonucleotides-mentioning
confidence: 99%
“…These stereospecificities are reversed with nuclease P1 (63). Therefore the phosphorothioates were separately digested with nuclease P1 and snake venom phosphodiesterase and the resulting deoxynucleoside products were analyzed by reverse phase HPLC (17,30). When "early" isomers were treated with the snake venom enzyme, a peak corresponding to dNMPs was observed by HPLC, whereas reaction with P1 gave a NsN unhydrolyzed dinucleotide peak (not shown).…”
Section: Synthesis Of Phosphorothioate-containing Oligonucleotides-mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have been extended to investigate reaction mechanisms involving restriction enzymes such as EcoRI (52) and EcoRV (53), DNA integration (54), and site-specific DNA recombination (55). All of these reactions proceed with an inversion of configuration as a result of a single nucleophilic substitution.…”
Section: Phosphorothioatesmentioning
confidence: 99%